Perbedaan Individu: Intelegensi dan Bakat serta Implikasinya dalam Pengajaran - Isnaini Isnaini; Nidya Fitri; Melisa Melisa; Arisco Mardiansyah; Hadi Purwanto (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims at determining individual differences from aspects of intelligence and talent and their implications for learning. These individual differences need to be given special treatment in order to identify problems that arise. Knowing the factors that influence individual differences can provide solutions and detect early on and appropriate treatment in accordance with the child’s development. This research uses literature study method by processing and analyzing a number of relevant literature. Data are analyzed, grouped, and interpreted to determine the factors that influence individual differences. The results showed that individual differences based on the aspects of intelligence and talent can be given attention from parents, encouraging expression, choosing a good school for children, and efforts to address individual differences in learning with open learning in children at school.